Not all inequalities are equal: differences in coverage across the continuum of reproductive health services. Issue 5 (3rd September 2019) - Sully, Elizabeth A; Biddlecom, Ann; Darroch, Jacqueline E
Abstract : Reducing inequalities in health service coverage is central to achieving the larger goal of universal health coverage. Reproductive health services are part of evidence-based health interventions that comprise a minimum set of essential health interventions that all countries should be able to provide. This paper shows patterns in inequalities in three essential reproductive health services that span a continuum of care—contraceptive use, antenatal care during pregnancy and delivery at a health facility. We highlight coverage gaps and their impacts across geographical regions, key population subgroups and measures of inequality. We focus on reproductive age women (15–49 years) in 10 geographical regions in Africa, Asia and Latin America and the Caribbean. We examine inequalities by age (15–19, 20–24, 25–34 and 35–49 years), household wealth quintile, residence (rural or urban) and parity. Data on service coverage and the population in need are from 84 nationally representative surveys. Our results show that dominant inequalities in contraceptive coverage are varied, and include large disparities and impact by age group, compared with maternal health services, where inequalities are largest by economic status and urban–rural residence. Using multiple measures of inequality (relative, absolute and population impact) not only helps to show if there are consistent patterns in inequalities but also whether few or many different approaches are needed to reduce these inequalities and where resources could be prioritised to reach the largest number of people in need.